Circular Economy Initiatives in Supply Chain: A Systematic Literature Review and Future Research Directions - Hemakshi Chokshi; Rohit Agrawal; Ashutosh Samadhiya; Anil Kumar (International Journal of Mathematical, Engineering and Management Sciences, 2023)
The concept of a circular economy (CE) entails developing a closed-loop system that strives to reduce waste, which adversely impacts the environment, while also minimising the use of resources (both natural and technical). The authors perform a thorough literature assessment of relevant papers using bibliometric and network analysis methodologies to identify the major components involved in a CE and solve the issues associated with implementing CE practices in the supply chain (SC). One of the objectives of this study is to determine current trends in SC based on the CE from 2013 to 2022. 101 articles are selected for in-depth analysis based on a bibliometric and network analysis approach. The review sheds light on the most important success factors of CE practices in SC across a variety of industries, as well as current and upcoming research trends. This review identifies research gaps and highlights additional theoretical approaches to the critical success factors of CE practices in the SC. The findings of this research will enable organisations to better understand the challenges and opportunities associated with CE practices and develop more efficient and sustainable SC strategies.